Arsenic sequestration in gold mine wastes under changing pH and experimental rewetting cycles. (January 2021) - Hoagland, Beth; Mosley, Luke; Russo, Tess; Kirby, Jason; Cullen, Cecilia; Fantle, Matthew S.; Raven, Mark; Fisher, Joshua
Abstract: Arsenic (As) release related to gold mining activity can alter surface water and sediment chemistry. However, the toxicity of As in mine wastes, which is controlled by the speciation, concentration, and bioavailability of As, depends on the geochemical conditions of the impacted environment (e.g., pH, Eh, climate, mineralogy, etc). This study investigates the mechanisms of As partitioning into, or out of, streambed sediments downstream of the Porgera Gold Mine in Papua New Guinea. Mine tailings at this site are treated with lime and discharged directly into the watershed, thus making them susceptible to interaction with rain water, reducing groundwaters, or acid rock drainage if it were to develop post mine-closure. Although lime treatment increases pH and effectively triggers the precipitation of most mining-derived trace metals from wastewaters, As can become more soluble at elevated pH. We conducted batch reactor experiments to simulate the effects of changing pH (4–10) and wetting/drying cycles on As interactions with lime-treated tailings and to understand potential As behavior following mine closure. Across the pH range investigated, lime-treated waste sediments and streambed sediments located downstream of the open pit mine effectively scavenged As from the water column. Specifically, the lime-treated tailings buffered the pH and enhanced interactions between dissolved As and sediment surfaces via surface complexation reactions on amorphous iron oxides, as suggested by surface complexation modeling and batch reactor experimental results. This As scavenging mechanism further counteracted the increased solubility of As at high pH. Based on wetting/drying cycle experiments, we inferred that lime-treated tailings subjected to repeated wetting/drying cycles rapidly desorbed As during the onset of rewetting, but sorbed As via an aluminum-bridging mechanism in subsequent wetting/drying cycles. These results highlight the importance of continued lime treatment to reduce As mobility in mine wastes following mine closure, particularly for mine sites where wastes are released directly into watersheds with no containment infrastructure. Highlights: Gold mine wastes treated with lime facilitated As removal via surface complexation. Lime-treatment enhances As sequestration by mine tailings from pH 4 to 10. Mineral saturation and Al-bridging influence [As] during wetting/drying cycles.